Brenton Goodman: capstone - Goodman, Brenton, artist (Colorado State University. Libraries, 2014)
The artist's statement: My work revolves around the process. I focus on the creation rather than the final product. I find it is the little details that really make the final product to begin with. My work is both greatly complex and simple at the same time. The beauty of creating a website by coding is I can create a user experience with visuals, navigation, and play, where the end user has no idea what went into it. My process is invisible to the naked eye and my goal is to make the user forget about how it was created. The website should just function as you would expect it to. The other aspect of my work is animation. There are many similarities between web design and animation in my mind, both requiring extreme concentration. One wrong number or object out of place and the entire project will fall apart. I like this tension and it keeps me engaged in my work. My animations use simple shapes created in Adobe Illustrator that are deconstructed in Adobe After Effects. Then I reconstruct them into familiar objects to tell a story. I like the idea of transformation and transition. I use both of these ideas when creating my animations. I want people to feel comfortable when viewing or using my work. It should feel familiar and it should work like you expect it to, but at the same time it is complex. My work is completely functional and it serves a purpose as my creative outlet but also a professional goals. Includes links to four videos.
Colorado State University Art Department capstone project.
Capstone contains the artist's list, images, and links for works.
Keywords: graphic design; photography; electronic art